Dramaturgia sztuki - Krajewska, Anna (Przestrzenie Teorii, 2019)
In this Introduction, the author discusses the other articles contained in this volume and attempts to present the processess involved in art as stage preformance of both human and non-human actors. She not only examines the objects and persons but also aesthetic categories and the mechanisms involving categories in art. The author proposes a new language that allows for the description of art as a phenomenon of entangled objects, subjects, media, processes and events.